Exploring the usability of simulated patient methodology in dental clinics in Western Australia: A pilot survey - Viduni Liyange; Xin Rong Low; Joon Soo Park; Hien C. Ngo; Rhonda Clifford; Liza Seubert (Wiley, 2024)
Abstract Objectives This study aimed to explore the dental staff knowledge of simulated patient methodology and support for its use to investigate dental staffs' triaging ability. Material and Methods Staff at dental practices in Western Australia were invited to participate in a cross‐sectional online questionnaire, consisting of demographic questions, questions on triaging, and knowledge of simulated patient methodology. Descriptive and parametric tests were undertaken for quantitative data; qualitative responses were thematically analyzed. Results Of the 100 participants, most were female (71%), aged 25−39 years (57%), dentists (46%), and worked in private practices (60%). While 82% of participants triaged dental appointment enquiries, only 26% had heard of simulated patient studies. The majority (66%) of participants spent 1−5 min when triaging appointments and less than half (29%) asked about medical history, aggravating or alleviating factors. Although there was a general positive attitude toward use of simulated patient methodology to investigate practice, some concerns were identified. Conclusions The findings of our exploratory study suggests that there may be a potential for utilizing simulated patient studies to improve the care of patients by dental receptionists in general dental practices.